A Roadmap Towards Standards for Neurally Controlled End Effectors - Andrew Y. Paek; Justin A. Brantley; Akshay Sujatha Ravindran; Kevin Nathan; Yongtian He; David Eguren; Jesus G. Cruz-Garza; Sho Nakagome; Dilranjan S. Wickramasuriya; Jiajun Chang; Md Rashed-Al-Mahfuz; Md. Rafiul Amin; et al. (IEEE Open Journal of Engineering in Medicine and Biology)
The control and manipulation of various types of end effectors such as powered exoskeletons, prostheses, and ‘neural’ cursors by brain-machine interface (BMI) systems has been the target of many research projects. A seamless “plug and play” interface between any BMI and end effector is desired, wherein similar user's intent cause similar end effectors to behave identically. This report is based on the outcomes of an IEEE Standards Association Industry Connections working group on End Effectors for Brain-Machine Interfacing that convened to identify and address gaps in the existing standards for BMI-based solutions with a focus on the end-effector component. A roadmap towards standardization of end effectors for BMI systems is discussed by identifying current device standards that are applicable for end effectors. While current standards address basic electrical and mechanical safety, and to some extent, performance requirements, several gaps exist pertaining to unified terminologies, data communication protocols, patient safety and risk mitigation.